2014
DOI: 10.1007/s11251-014-9334-5
|View full text |Cite
|
Sign up to set email alerts
|

Child predictors of learning to control variables via instruction or self-discovery

Abstract: We examined the role child factors on the acquisition and transfer of learning the control of variables strategy (CVS) via instruction or self-discovery. Seventy-six fourth graders and 43 sixth graders were randomly assigned to a group receiving direct CVS instruction or a discovery learning group. Prior to the intervention, cognitive, scientific, and linguistic child factors were assessed. Acquisition and transfer of CVS knowledge were measured before and after intervention. Outcomes showed that CVS acquisiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 26 publications
9
45
1
1
Order By: Relevance
“…It has been shown that CVS skills can improve in children of the upper primary grades after a single short training. Children that received this instruction showed stronger improvements in inquiry abilities compared to a group of children in a free exploration condition, where no instruction on experimentation skills were given (Wagensveld, Segers, Kleemans, & Verhoeven, 2015). This result has been established consistently, as shown by a review of 72 direct CVS instructions (Schichow, Croker, Zimmerman, Höffler, & Härtig, 2016).…”
Section: Direct Instruction Of Scientific Reasoning Abilitiesmentioning
confidence: 63%
“…It has been shown that CVS skills can improve in children of the upper primary grades after a single short training. Children that received this instruction showed stronger improvements in inquiry abilities compared to a group of children in a free exploration condition, where no instruction on experimentation skills were given (Wagensveld, Segers, Kleemans, & Verhoeven, 2015). This result has been established consistently, as shown by a review of 72 direct CVS instructions (Schichow, Croker, Zimmerman, Höffler, & Härtig, 2016).…”
Section: Direct Instruction Of Scientific Reasoning Abilitiesmentioning
confidence: 63%
“…Besides attentional control, nonverbal reasoning related to game efficiency. Many types of reasoning have been found to be involved in scientific thinking, such as nonverbal reasoning ( Van der Graaf, et al, 2015), syllogistic reasoning (Wagensveld, et al, 2015), and general fluid ability (Mayer, Sodian, Koerber, & Swippert, 2014). As Dunbar and Klahr (2012) have…”
Section: Discussionmentioning
confidence: 99%
“…reasoning) skills. Correct experimentation has been linked to vocabulary and syllogistic reasoning (Wagensveld, et al, 2015). Vocabulary can help children to understand scientific principles.…”
Section: Discovering the Laws Of Physics With A Serious Gamementioning
confidence: 99%
See 1 more Smart Citation
“…From some existing learning models, one way to deal with the above problem is by guided-discovery learning model. Discovery learning can be defined as the learning that takes place when the student is not presented with the subject matter in the final form, but rather is required to organize it himself (Janssen, Westbroek, & van Driel, 2014;Mayer, 2004;Wagensveld, Segers, Kleemans, & Verhoeven;2015).…”
Section: Introductionmentioning
confidence: 99%